White Coffin comes alive - Abd Razak, Dzulkifli (2010)
MANY still recall The White Coffin Project initiated by Universiti Sains Malaysia (USM) students a few years ago. This modest effort to champion sustainability met with unexpected public endorsement and took the local media by storm. Many campuses in Malaysia and abroad followed USM's lead and became polystyrenefree as well. USM was recognised for its efforts at the Healthy Cities Alliance Conference in Japan and received the Award for Creative Developments in Healthy Cities for its innovative initiative.